Symbolic expression in Pleistocene Sahul, Sunda, and Wallacea. (1st October 2019) - Langley, Michelle C.; Clarkson, Chris; Ulm, Sean
Abstract: The pace of research undertaken in Sunda (Southeast Asia) through to Sahul (Greater Australia) has increased exponentially over the last three decades, resulting in spectacular discoveries ranging from new hominin species, significant extension to the age for first human occupation in the region, as well as the identification of what is currently the oldest known rock art in the world. These breakthroughs cast the archaeological record of complexity in Sunda, Sahul, and Wallacea in an entirely different light to that of several decades ago, placing it on an equal footingto that of Africa, Asia, and Europe. The archaeological record of these regions now points to rich and diverse early modern human ( Homo sapien ) societies engaged in complex symbolic and technological behaviours demonstrating capacities for innovation and self-expression found in all modern human groups now around the globe. Here we provide a comprehensive review of all Pleistocene symbolic evidence reported for Sahul, Sunda, and Wallacea to date. We explore how recent findings have changed our perceptions of the first modern human colonists and our understanding of the origins and development of the rich and diverse cultures that arose in each region through time. Graphical abstract: Image 1 Highlights: We review all evidence for Pleistocene symbolic behaviour in Sahul, Sunda, Wallacea. We explore how recent findings have changed our perceptions of these regions. We overturn long-held notions that Sahul, Sunda, and Wallacea were static and lacked cultural dynamism.